Caracterização de uma proteína rica em glicinas e da paramiosina do carrapato Rhipicephalus microplus - Leal, Bruna Ferreira (2017)
Rhipicephalus microplus is a tick that infests preferably bovines and cause a great damage in the livestock. The main control method against ticks is the use of acaricides, which lead to the emergence of resistant populations, in addition to increasing costs and risk of contamination of meat, milk and environment. Thus, vaccine antigens have been identified and characterized as an alternative to acaricides. Salivary molecules of hematophagous parasites can inhibit responses associated to homeostasis and modulate the host immune system and, therefore, are options in the search for anti-tick vaccines. This work characterized a glycine rich-protein and the paramyosin of R. microplus. Glycine rich-proteins are secreted in tick saliva and are essential in the attachment and blood feeding. Paramyosin is able to evade the host immune system and proved to be an important allergen of mites and vaccine antigen against helminths. The cDNA and amino acid sequences of the R. microplus glycine rich-protein (RmGRP) were identified and analyzed, revealing two distinct portions of the protein (glycine residues presented dispersed in the N-terminal region and in repeated patterns along the C-terminal region). Cloning, expression and purification of RmGRP were performed and the recombinant protein was tested for recognition by sera from naturally and experimentally infested bovines, indicating their antigenicity, but also displaying a high heterogeneity in protein recognition between individuals and among infestations in the same individual. In addition, recombinant RmGRP was recognized by sera from rabbits immunized with saliva and salivary gland from partially and fully engorged females and eggs, but not from sera from rabbits immunized with gut. Expression of the gene encoding RmGRP (rmgrp) in different female tissues and tick development stages was evaluated by qRT-PCR. Gene transcription was found in eggs, larvae, adult males, salivary glands, fat bodies and ovaries of partially and fully engorged females, with the highest expression levels in 1-day-old larvae and salivary glands of fully engorged females. rmgrp was not expressed in 3- and 6-day-old eggs and in guts of partially and fully engorged females, corroborating to the aforementioned result. Effects of RNAm silencing corresponding to RmGRP and RmPRM were evaluated, which resulted in egg laying reduction in the group in which the RmPRM gene was silenced and in the reduction of larval hatching rate in the two groups. Therefore, it is suggested that both proteins are important during larval development, but only RmPRM is required in egg formation and/or laying. Cloning of the coding DNA regions and expression of N-terminal, internal and Cterminal fragments of R. microplus paramyosin (RmPRM) in Escherichia coli and of the complete RmPRM in Pichia pastoris were confirmed by SDS-PAGE and western-blot. From the data obtained, both RmGRP and RmPRM have characteristics that make them possible candidates to compose a cocktail vaccine against R. microplus.